Teknik Token Ekonomi dalam Mengenal Konsep Uang pada Anak dengan Retardasi Mental - Nuzul Khaira; Julian Putri Alhidaya; Shinta Ayu Wulandari; Reza Anugrah; Tesa Anggraini; Intan Denata (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to introduce the concept of money to children with mild mental retardation by using an economic token. The subject of this study was a 10 year old girl with mild mental retardation. This study collects data using observation by monitoring behavior. The technique used in this modification program is in the form of an economic token in order to bring up the desired stimulus response. Initial data collection or baseline was carried out in 7 sessions and then continued with intervention for 5 days with a total of 10 sessions. The results of the study show that the token economy technique can improve the ability of mentally retarded children to recognize the concept of money.